PENGEMBANGAN STRATEGIC BUSINESS UNIT PERHUTANI UNIT III JAWA BARAT DAN BANTEN - Rurin Wahyu Listriana; Meika Syahbana Rusli; Wati Hermawati (School of Business, Bogor Agricultural University (SB-IPB), 2013)
ABSTRACTThis study aimed to 1) analyze the innovation and competitiveness ability of Strategic Business Unit (SBU) in the KBM (independent business unit) industri and 2) formulate alternative policies that can enhance company innovation and competitiveness. The study was conducted at KBM Industri and SBU within the KBM industri. The information and data was obtained through interviews and distributing questionnaires to 10 respondents. Respondents were chosen based on their expertise and or experience. Data processing techniques used the SWOT analysis and Analytic Hierarchy Process (AHP). Results of this study shows that KBM Industri Unit III have the power and the opportunity to expand, increase growth, and achieve maximum progress by improving the quality, developing new products, improving processes and increasing access to wider market. The potential innovation can also be seen from the process-product innovation, knowledge-skills innovation and method-system innovation. In the KBM Industri Unit III, those potential covers the raw materials, process equipment and products. The improvement of company's innovation was influenced by the main factor organization with the value 0,436 and the most influential factors of marketing with a value 0,398, while the ultimate goal is the improvement of the process with the value 0,756. The improvement of the company's innovation strategy is through strategy priority, namely cooperation with other /external parties weighted by 0,703 and optimizing own capabilities of the research or conducting institutions development research weighted by 0,297.Keywords: SBU, KBM Industri, Innovation, AHP, SWOTABSTRAKPenelitian ini bertujuan 1) menganalisis kemampuan inovasi dan daya saing Strategic Business Unit (SBU) di Kesatuan Bisnis Mandiri (KBM) Industri dan 2) merumuskan kebijakan alternatif yang dapat meningkatkan inovasi dan daya saing perusahaan. Penelitian dilakukan pada KBM Industri dan SBU yang ada didalam KBM Industri. Informasi dan data didapat melalui wawancara dan penyebaran kuesioner kepada responden dengan jumlah sebanyak 10 orang. Responden yang diambil bersangkutan dengan topik penelitian ini dan mempunyai keahlian dan atau pengalaman pada bidang yang dikaji. Teknik pengolahan data menggunakan analisis SWOT dan analytic hierarchy process. Kesimpulan penelitian ini adalah KBM Industri Unit III memiliki kekuatan dan peluang untuk melakukan ekspansi, memperbesar pertumbuhan dan meraih kemajuan secara maksimal dengan meningkatkan kualitas, mengembangkan produk baru, memperbaiki proses dan meningkatkan akses ke pasar yang lebih luas. Potensi inovasi perusahaan juga dapat dilihat dari inovasi proses-produk, inovasi pengetahuan-ketrampilan dan inovasi metode-sistem. Pada KBM Industri Unit III potensi tersebut meliputi potensi bahan baku, peralatan proses dan produk Peningkatan inovasi perusahaan dipengaruhi oleh faktor utama organisasi dengan nilai 0,436 dan aktor yang paling berpengaruh adalah sumber daya manusia dengan nilai 0,398. Tujuan utamanya adalah perbaikan proses dengan nilai 0,756. Peningkatan inovasi perusahaan dapat dicapai melalui prioritas strategi, yaitu kerja sama dengan pihak lain/ekternal dengan bobot 0,703 dan mengoptimalkan penelitian dan pengembangan atau membuat penelitian dan pengembangan yang berdekatan dengan SBU dengan bobot 0,297. Kata kunci: SBU, KBM Industri, Inovasi, AHP, SWOT